Tests and Procedures for Measuring Endurance, Strength, and Power in Climbing—A Mini-Review - Stien, Nicolay; Saeterbakken, Atle Hole; Andersen, Vidar (Frontiers in Sports and Active Living, 2022)
The interest in climbing is rapidly growing among professional and recreational athletes and will for the first time be included in the 2021 Tokyo Olympics. The sport has also gained increased scientific attention in the past decades. Still, recommendations for testing procedures to predict climbing performance and measure training effects are limited. Therefore, the aim of this mini-review is to provide an overview of the climbing-specific tests, procedures and outcomes used to examine climbing performance. The available literature presents a variety of tests and procedures. While the reliability of some tests has been examined, measures of validity are scarce, especially for climbing-specific endurance tests. Moreover, considering the possible combinations of climbing performance levels, disciplines, and tests, substantial gaps in the literature exist. Vague descriptions of the participants in many studies (e.g., not specifying preferred discipline, performance level, experience, and regular climbing and training volume) further limit the current knowledge and challenge comparisons across studies. Regarding contraction types, dynamic strength- and power-tests are underrepresented in the literature compared to isometric tests. Studies exploring and reporting the validity and reliability of climbing-specific tests are warranted, and researchers should strive to provide a detailed description of the study populations in future research.